Sunday

February 1, 2015

February 1, 2015

Posted by **David** on Saturday, July 27, 2013 at 4:33pm.

x''+x=cos(3t), x(0)=x'(0)=0

- calculus -
**Steve**, Saturday, July 27, 2013 at 6:03pmL{x"} = s^2*F(s) - s*f(0) - f'(0)

= s^2*F(s)

so,

s^2 F(s) + F(s) = s/(s^2+9)

F(s) = s/((s^2+9)(s^2+1))

= 1/8 (s/(s^2+1) - s/(s^2+9))

f(t) = 1/8 (cos(t) - cos(3t))

check:

x' = 1/8 (3sin(3t)-sin(t))

x" = 1/8 (9cos(3t)-cos(t))

x'+x = 1/8 (8cos(3t)) = cos(3t)

**Answer this Question**

**Related Questions**

Calculus-HELP!!! - Find the Laplace transform of: f(t) = cos^(2)(2t)

Calculus-HELP!!! - Find the Laplace transform of: f(t) = cos^(2)(2t)

calc 2 - (last one) ... Let f(t) be a function defined for all values of t. The...

Calc2 - Let f(t) be a function defined for all values of t. The Laplace ...

advanced math - what is the Laplace transform of e^4t(cos 2t) ?

college math - the Laplace transform of e^4t(cos 2t)?? please i need help. ...

Calculus - Find the Laplace transform of: f(t)=t-2e^(3t)

Calculus - Find the inverse Laplace transform of: F(s)=3/(s-4)

Calculus-HELP!!! - Find the inverse Laplace transform of: F(s)=2/s^4

calculus - Find the inverse Laplace transform of the function: F(s)=1/(s(s+1)(s+...